2016
DOI: 10.1002/hbm.23220
|View full text |Cite
|
Sign up to set email alerts
|

Spectral and spatial changes of brain rhythmic activity in response to the sustained thermal pain stimulation

Abstract: The aim of this study was to investigate the neurophysiological correlates of pain caused by sustained thermal stimulation. A group of 21 healthy volunteers was studied. 64-channel continuous EEG was recorded while the subject received tonic thermal stimulation. Spectral changes extracted from EEG were quantified and correlated with pain scales reported by subjects, the stimulation intensity, and the time course. Network connectivity was assessed to study the changes in connectivity patterns and strengths amon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

10
19
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 55 publications
(30 citation statements)
references
References 115 publications
(182 reference statements)
10
19
0
1
Order By: Relevance
“…Although these frequencies have been implicated in the top‐down signaling of predictions (Fries, ; Michalareas et al, ; Ploner et al, ), the present findings indicate that the alpha connectivity between sensorimotor and prefrontal cortex might reflect increased bottom‐up rather than top‐down signaling of potentially nociceptive information as our recent work suggests (Nickel, May, Tiemann, Schmidt, et al, ). These results are in line with previous findings showing that directed functional connectivity is enhanced between somatosensory and medial frontal cortex during pain (Huishi Zhang et al, ). Moreover, the findings are in accordance with mounting evidence for an important role of the medial prefrontal cortex for the encoding of chronic (Baliki et al, ; Hashmi et al, ; Vachon‐Presseau et al, ) and tonic experimental pain (Nickel, May, Tiemann, Schmidt, et al, ; Schulz et al, ).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Although these frequencies have been implicated in the top‐down signaling of predictions (Fries, ; Michalareas et al, ; Ploner et al, ), the present findings indicate that the alpha connectivity between sensorimotor and prefrontal cortex might reflect increased bottom‐up rather than top‐down signaling of potentially nociceptive information as our recent work suggests (Nickel, May, Tiemann, Schmidt, et al, ). These results are in line with previous findings showing that directed functional connectivity is enhanced between somatosensory and medial frontal cortex during pain (Huishi Zhang et al, ). Moreover, the findings are in accordance with mounting evidence for an important role of the medial prefrontal cortex for the encoding of chronic (Baliki et al, ; Hashmi et al, ; Vachon‐Presseau et al, ) and tonic experimental pain (Nickel, May, Tiemann, Schmidt, et al, ; Schulz et al, ).…”
Section: Discussionsupporting
confidence: 93%
“…These results are in line with previous findings showing that directed functional connectivity is enhanced between somatosensory and medial frontal cortex during pain (Huishi Zhang et al, 2016). Moreover, the findings are in accordance with mounting evidence for an important role of the medial prefrontal cortex for the encoding of chronic (Baliki et al, 2006;Hashmi et al, 2013;Vachon-Presseau et al, 2016) and tonic experimental pain (Nickel, May, Tiemann, Schmidt, et al, 2017;Schulz et al, 2015).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The increased temporal and spatial resolution of this method makes it desirable to further probe for markers of disease severity and potentially chronic pain that can be used to improve treatment strategies. Non-invasive imaging studies have shown it is possible to use biomarkers to objectively rate acute pain in healthy controls (Zhang et al, 2016, Wager et al, 2013). Similar techniques could be applied to chronic pain patients so that pain can be objectively measured to improve treatment and reduce the risk of opioid therapy.…”
Section: Discussionmentioning
confidence: 99%
“…However, most of these studies have investigated the effects of phasic pain stimuli. To mimic responses triggered during chronic pain [26], there are a growing number of studies using tonic thermal stimuli [27]–[31]. …”
mentioning
confidence: 99%